GREEN CHEMISTRY INNOVATIONS IN PLASTIC DEGRADATION AND RECYCLING (Journal of Medical & Health Sciences Review, 2025)
Background: Plastic pollution is a major environmental problem, with conventional plastics remaining in ecosystems for hundreds of years. Innovative solutions for plastic damage and recycling under the green chemistry concept can significantly reduce ecological threats and support the switch to sustainable waste disposal. That said, the continued success of these innovations in terms of their effectiveness, scalability, and adoption remains an area of active research and policy debate.Objective: This study provides a comprehensive overview of recent progress made toward green chemistry strategies that maximize plastic degradation and recycling. This is primarily to evaluate the performance of enzyme-based, microbial, and chemical recycling technologies, as well as the challenges and policy implications associated with them.Methods: Peer-reviewed studies published in the last five years were identified through a comprehensive search from several academic databases (Scopus, Web of Science, Google Scholar, ScienceDirect, and SpringerLink). Studies were filtered by methodological, topical, and scientific rigor based on strict inclusion and exclusion criteria. Data extraction was performed with the use of standardized quality assessment tools to ensure reliability and viability.Results: According to our findings, the use of enzyme and microbial-based plastic degrading enzymes has been predicted to lead to polymeric structure degradation most immediately. Advancements toward industrial applications of chemical recycling methods, including depolymerization and solvolysis, are being made. Nonetheless, expensive costs, infrastructural constraints, and regulatory obstacles pose challenges to widespread adoption. Furthermore, environmental safety, efficiency, and economic feasibility need to be investigated.Conclusion: Greener approaches showing great potential for plastic pollution solution The field of green chemistry has progressively found solutions to the problem of plastic waste challenges. Yet, to gain widespread acceptance, economic and regulatory barriers must be overcome. Future studies should focus on maximizing degradation performance, improving waste management systems, and establishing laws and regulations to promote eco-friendly plastic utilization. Future research may consider scalable solutions that meet both environmental objectives and economic imperatives.